Apprehension-Based Training: A Novel Treatment Concept for Anterior Shoulder Dislocation - A Case Report - Alon Rabin; Livneh Noyman; Noa Yaakobi; Efi Kazum (North American Sports Medicine Institute, 2024)
# Background and Purpose Conservative management of anterior shoulder dislocation (ASD) is associated with greater recurrence compared with surgical management. Current rehabilitation protocols may not adequately challenge shoulder stability to encourage adaptive coping strategies. Apprehension-based training (ABT) is a new treatment concept derived from the supine moving apprehension test (SMAT), a previously validated performance measure among patients with ASD. The purpose of this case report is to describe the application of ABT in a patient with recurrent ASD. # Study Design Case report # Case Description The subject was a 23-year-old male with bilateral recurrent ASD. The subject underwent a 17-week exercise program involving gradual exposure to increased anterior instability loads based on the SMAT movement pattern. The Western Ontario Shoulder Instability Index (WOSI), Patient-Specific Functional Scale (PFPS), Tampa Scale of Kinesiophobia, SMAT, shoulder internal and external rotation muscle strength were measured via hand-held dynomometry before and after training. # Outcomes Following treatment, clinically meaningful gains in quality of life (WOSI) and shoulder function (PSFS) were noted. Kinesiophobia decreased, SMAT and shoulder internal rotator strength increased beyond their respective minimal detectable change. Four months after treatment, quality of life and shoulder function remained improved, and the subject reported a reduced rate of ASD. # Discussion Apprehension-based training involving gradual exposure to shoulder instability loads may hold potential for improving the management of patients with ASD. Further testing of this concept is warranted. # Level of Evidence 4, single case report